Pelestarian dan Pemanfaatan Warisan Budaya Pura Giri Natha sebagai Daya Tarik Wisata Religi di Timor Leste - Anak Agung Ayu Dewi Larantika; I Made Mardika; Toto Noerasto (Postgraduated Community Service Journal, 2025)
This community service activity aims to preserve and utilize the cultural heritage of Pura Giri Natha in Taibesi, Dili, Timor-Leste, as a religious tourism attraction. Pura Giri Natha is the largest Hindu temple in Timor-Leste and serves as a symbol of the cultural ties between Bali and Timor-Leste. The primary challenges identified include the absence of a formal temple community group (pengyungsung) and infrastructure that has not yet been organized for spiritual tourism. The proposed solutions involve establishing a temple management group through counseling and institutional mentoring, as well as organizing the temple area based on best practices from temple tourism management in Bali. The results demonstrate the formation of an active management group and improvements in infrastructure arrangement. This activity contributes to cultural preservation, local economic empowerment, and the development of sustainable tourism.